ANATOMICAL VARIATIONS OF THE RENAL ARTERIES IN HUMANS. - RAJESH R. VIJAY KUMAR; ABHAY B. MANE (International Journal of Pharma and Bio Sciences, 2013)
Renal artery variations are becoming more important due to the gradual increase in interventional radiological procedures, urological and vascular operations, and renal transplantation. Such variations have great implication when surgery is indicated. Increase in frequency of renal diseases and renal transplants, there is a need of research work aimed at better and accurate knowledge of variations of the blood vessels supplying the kidneys. OBJECTIVE: To study the variations of renal arteries in various cadavers based on the level and source of origin, course and relations. The origin of right renal arteries from the aorta was between the upper margin of L1 and lower margin of L2 vertebra in 96.7% of the specimen. The most common location for the origin of renal artery was at the level of L1- L2 intervertebral disc. Renal artery variations included abnormal origin at the level of L3 vertebra in 3.3%, abnormal course and relations in 6.6% of the specimen.